I have been trying to do this question but I'm completely lost.

Be $f(x,y)$ a differentiable function, the maximum value of $Duf$(0,2) is equal to 2 and occurs when $u = (\frac{\sqrt 2}{2},\frac{\sqrt 2}{2})$.
If $x(s,t) = s²t$, $y(s,t) = 2se^t$ and $F(s,t) = f(x(s,t),y(s,t))$ then $\frac{\partial F}{\partial t}$(1,0) is:

a)2$\sqrt 2$
b)3$\sqrt 2$
d)$\sqrt 2$
e)3$\frac{\sqrt 2}{2}$

I did the chain rule: $\frac{\partial F}{\partial t} = \frac{\partial F}{\partial x}*\frac{\partial x}{\partial t} + \frac{\partial F}{\partial y}*\frac{\partial y}{\partial t}$

And also the derivatives:
$\frac{\partial x}{\partial t} = s² = 1$
$\frac{\partial y}{\partial t} = 2se^t = 2$

Then I put everything together: $\frac{\partial F}{\partial t}(1,0) = \frac{\partial F}{\partial x}*1 + \frac{\partial F}{\partial y}*2$

After this I don't know how to proceed.

If there are any english mistakes then I am sorry. It isn't my first language.


Your english was good! (It would've been better to say "Let $f(x,y)$ be a ..." instead, but this was the only mistake)

The directional derivative of $f$ at $(0,2)$ in the direction of $\underline{u}$ means

$$\frac{\sqrt{2}}{2}\frac{\partial f}{\partial x}\Bigg{\vert}_{(0,2)}+\frac{\sqrt{2}}{2}\frac{\partial f}{\partial y}\Bigg{\vert}_{(0,2)}=2\implies\frac{\partial f}{\partial x}\Bigg{\vert}_{(0,2)}+\frac{\partial f}{\partial y}\Bigg{\vert}_{(0,2)}=2\sqrt{2}$$

We know that $\underline{u}$ maximizes the directional derivative at $(0,2)$, which means that the angle between $\nabla f(0,2)$ and $\underline{u}$ is $0$. Then there exists a vector $\underline{v}$ such that $\underline{u}\cdot\underline{v}=0$ which means


We can find $\underline{v}$ easily, the only condition is that $\underline{u}\cdot\underline{v}=0$



$$\frac{\sqrt{2}}{2}\frac{\partial f}{\partial x}\Bigg{\vert}_{(0,2)}-\frac{\sqrt{2}}{2}\frac{\partial f}{\partial y}\Bigg{\vert}_{(0,2)}=0\implies\frac{\partial f}{\partial x}\Bigg{\vert}_{(0,2)}=\frac{\partial f}{\partial y}\Bigg{\vert}_{(0,2)}$$

Then we can conclude that

$$\frac{\partial f}{\partial x}\Bigg{\vert}_{(0,2)}=\sqrt{2}$$


$$\frac{\partial F}{\partial t}\Bigg{\vert}_{(1,0)}=\frac{\partial f}{\partial x}\Bigg{\vert}_{(0,2)}\frac{\partial x}{\partial t}\Bigg{\vert}_{(1,0)}+\frac{\partial f}{\partial y}\Bigg{\vert}_{(0,2)}\frac{\partial y}{\partial t}\Bigg{\vert}_{(1,0)}$$

Where the partials with respect to $x$ and $y$ are evaluated at $(0,2)$ because $x(1,0)=0$ and $y(1,0)=2$

$$\boxed{\therefore\frac{\partial F}{\partial t}\Bigg{\vert}_{(1,0)}=3\sqrt{2}}$$

Using the chain rule means we have $z=f(x,y)$ with $x=x(s,t)$ and $y=y(s,t)$ so then

$$\frac{\partial z}{\partial t}=\frac{\partial f}{\partial x}\frac{\partial x}{\partial t}+\frac{\partial f}{\partial y}\frac{\partial y}{\partial t}$$

The way you tried to use the chain rule would not work because you defined

$$F(s,t)=f(x(s,t),y(s,t))\equiv g(s,t)$$

where $g$ is just some function of $s$ and $t$. So it wouldn't make sense to take partials of $F$ with respect to $x$ and $y$ because they've been already substituted and you would just get $0$.

| cite | improve this answer | |

You are given that the maximum value of $D_uf(0,2)$ is $2$, occurring at $u=(\frac{\sqrt{2}}{2},\frac{\sqrt{2}}{2})$. This means that $$\begin{aligned}2&=\nabla f(0,2)\cdot u\\&=(\frac{\partial f(0,2)}{\partial x},\frac{\partial f(0,2)}{\partial y})\cdot(\frac{\sqrt{2}}{2},\frac{\sqrt{2}}{2})\end{aligned}\tag{1}$$ and as $D_uf(0,2)$ has a maximum value of $2$, the direction of the derivative vector $(\frac{\partial f(0,2)}{\partial x},\frac{\partial f(0,2)}{\partial{y}})$ will be the same as that of $u$, so that $$\frac{\partial f(0,2)}{\partial x}=\frac{\partial f(0,2)}{\partial y}$$ thus from equation $(1)$ we have $$\frac{\partial f(0,2)}{\partial x}=\frac{\partial f(0,2)}{\partial y}=\sqrt{2}$$ Going back to the chain rule you have written, this can be written in terms of the derivative of function $f(x,y)$:- $$\begin{align}\frac{\partial F(0,1)}{\partial t}&=\frac{\partial f(0,2)}{\partial t}\\&=\frac{\partial f(0,2)}{\partial x}\frac{\partial x}{\partial t}+\frac{\partial f(0,2)}{\partial y}\frac{\partial y}{\partial t}\\&=\frac{\partial f(0,2)}{\partial x}\times1+\frac{\partial f(0,2)}{\partial y}\times2\\&=3\sqrt{2}\end{align}$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.